2010
DOI: 10.1007/s15010-010-0047-7
|View full text |Cite
|
Sign up to set email alerts
|

Educating healthcare workers to optimal hand hygiene practices: addressing the need

Abstract: The education of healthcare workers is essential to improve practices and is an integral part of hand hygiene promotional strategies. According to the evidence reviewed here, healthcare worker education has a positive impact on improving hand hygiene and reducing healthcare-associated infection. Detailed practical guidance on steps for the organization of education programmes in healthcare facilities and teaching-learning strategies are provided using the World Health Organization (WHO) Guidelines for Hand Hyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 64 publications
1
30
1
1
Order By: Relevance
“…14 But in spite of the available evidence, implementation is still a problem both for HCOs and HCWs. [15][16][17] It is therefore essential to promote competence-based training of specialists in IC/HH, as well as HCWs more generally, to make them aware of HCAI risks and capable of implementing appropriate recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…14 But in spite of the available evidence, implementation is still a problem both for HCOs and HCWs. [15][16][17] It is therefore essential to promote competence-based training of specialists in IC/HH, as well as HCWs more generally, to make them aware of HCAI risks and capable of implementing appropriate recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…2008 ;Wachter and Pronovost 2009 ;Mathai et al . 2010 ) highlight that attitudes of HCW often lack an acceptance of personal responsibility for correct IC/HH and the need for sustained improvements in IC/HH practices, showing there is still room for improvement and as a consequence such training must be considered a priority.…”
Section: Educationmentioning
confidence: 99%
“…Safdar & Abad (2008) reviewed educational interventions to prevent HCAI and concluded that educational interventions may reduce HCAI considerably. A systematic review by Mathai et al (2010) looked at educational interventions to improve hand hygiene but did not explicitly focus on compliance, and found that healthcare professional education has a positive impact on improving hand hygiene and reducing healthcare-associated infection. Aboelela et al (2007) considered the effectiveness of bundled behavioural interventions on reducing HCAI.…”
Section: Practice Pointsmentioning
confidence: 99%